Krimper Enforces an Antisense Bias on piRNA Pools by Binding AGO3 in the Drosophila Germline. - Sato, K.; Iwasaki, Y.W.; Shibuya, A.; Carninci, P.; Tsuchizawa, Y.; Ishizu, H.; Siomi, M.C.; Siomi, H. (Molecular Cell, 2015)
Piwi-interacting RNAs (piRNAs) suppress transposon activity in animal germ cells. In the Drosophila ovary, primary Aubergine (Aub)-bound antisense piRNAs initiate the ping-pong cycle to produce secondary AGO3-bound sense piRNAs. This increases the number of secondary Aub-bound antisense piRNAs that can act to destroy transposon mRNAs. Here we show that Krimper (Krimp), a Tudor-domain protein, directly interacts with piRNA-free AGO3 to promote symmetrical dimethylarginine (sDMA) modification, ensuring sense piRNA-loading onto sDMA-modified AGO3. In aub mutant ovaries, AGO3 associates with ping-pong signature piRNAs, suggesting AGO3's compatibility with primary piRNA loading. Krimp sequesters ectopically expressed AGO3 within Krimp bodies in cultured ovarian somatic cells (OSCs), in which only the primary piRNA pathway operates. Upon krimp-RNAi in OSCs, AGO3 loads with piRNAs, further showing the capacity of AGO3 for primary piRNA loading. We propose that Krimp enforces an antisense bias on piRNA pools by binding AGO3 and blocking its access to primary piRNAs.